2019
DOI: 10.1093/heapol/czz091
|View full text |Cite
|
Sign up to set email alerts
|

Reaching rural communities through ‘Healthy Entrepreneurs’: a cross-sectional exploration of community health entrepreneurship’s role in sexual and reproductive health

Abstract: The purpose of the current study was to explore the association between community health entrepreneurship and the sexual and reproductive health status of rural households in West-Uganda. We collected data using digital surveys in a cluster-randomized cross-sectional cohort study. The sample entailed 1211 household members from 25 randomly selected villages within two subcounties, of a rural West-Ugandan district. The association between five validated sexual and reproductive health outcome indicators and expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The telehealth approach in this study was designed in specific circumstances, which allowed for rapid implementation and scale-up. In Uganda there was a well-functioning network of active CHWs, equipped with a smart phone, and supported during monthly cluster meetings [ 14 , 19 ]. At the start of the pandemic, many in the public health sector were very concerned about the predicted wave of critically ill patients and decision makers were ready to support telehealth as a solution for informing and supporting CHWs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The telehealth approach in this study was designed in specific circumstances, which allowed for rapid implementation and scale-up. In Uganda there was a well-functioning network of active CHWs, equipped with a smart phone, and supported during monthly cluster meetings [ 14 , 19 ]. At the start of the pandemic, many in the public health sector were very concerned about the predicted wave of critically ill patients and decision makers were ready to support telehealth as a solution for informing and supporting CHWs.…”
Section: Discussionmentioning
confidence: 99%
“…In Kampala, a call-center was set up with a team of nurses and doctors who supported a network of approximately 3,500 community health workers operating in 23 rural districts. These CHWs were part of the regular public health system and were simultaneously supported by a non-profit organization called Healthy Entrepreneurs (HE) [ 18 , 19 ]. HE uses an approach that draws upon the principles of micro entrepreneurship to support CHWs who are active in rural and remote communities [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we focus on a novel approach aimed at making CHW programmes more effective and sustainable, by using the principles of microentrepreneurship. In this approach, regular CHWs are trained to become community health entrepreneurs (CHEs) who continue their standard community health activities within the public health system, while making a modest income from selling basic health products, such as antimalaria medicine, oral rehydration salts (ORS), soap and fortified foods 12. The CHEs thus become microentrepreneurs and purchase these products through a social enterprise and earn a margin on each product sold.…”
Section: Introductionmentioning
confidence: 99%
“…The first study is a large randomised controlled trial, which showed a substantial reduction (27%) in child mortality in (semi)urban setting 13. A second, cluster-randomised cross-sectional cohort study showed higher use of modern contraceptives and more knowledge about sexual and reproductive health in communities in rural areas 12. A recent scoping review which included nine other studies recommends social enterprise as a viable model for providing primary healthcare in resource poor areas 14…”
Section: Introductionmentioning
confidence: 99%